RNA‐Sequencing in Elucidating Immune Responses to Haemonchus contortus Infection in Small Ruminants Systematic Review - Ndaba, Bongeka Sylvia (Parasite Immunology, 2025)
ABSTRACT Haemonchus contortus poses a major threat to small ruminant production in subtropical regions worldwide. Unfortunately, there is growing anthelmintic resistance, and the only licensed vaccine has limitations. This paper aimsto review the use of RNA‐sequencing in understanding the immune responses of small ruminants to H. contortus infection, focusing on identifying differentially expressed genes and elucidating key immune pathways associated with resistance and susceptibility. This review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses Statement guidelines and Population, Intervention, Control, and Outcome framework covering publications from January 2015 to December 2023. RNA‐seq identified the activation of key immune pathways, such as Th1/Th2, NK cell, B cell receptor signalling, MAPK, CAMs, and TNF signalling. There was upregulation of a range of PRRs, including TLRs and CLECs, in the resistant sheep, suggesting a crucial role for trained innate immune cells in resistance. However, there are no direct comparisons of TLR and CLEC expression between resistant and susceptible goats. This shows that there is a gap in understanding of the immune response mechanisms in goats. Addressing these knowledge gaps will lead to the development of more effective and sustainable control strategies.